MAKNA KONTEKS DALAM CERPEN “SENYUM KARYAMIN” KARYA AHMAD TOHARI (PENDEKATAN LINGUISTIK SISTEMIK FUNGSIONAL) - Aristiani, Ani; Baehaqie, Imam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Literature is an art form studied in schools at both primary and secondary levels. One type of literary work studied at the junior high school level is the short story. Short stories often employ language that requires interpretation beyond mere structural meaning, necessitating the integration of contexts outside of the language itself. Therefore, a linguistic approach is needed to interpret short stories, one of which is Systemic Functional Linguistics (SFL). This study aims to analyzed and describe how the SFL approach interprets language within a short story. The research method used is descriptive qualitative, providing detailed and systematic explanations. The findings indicate that, contextually, the meaning of a short story can be viewed through cultural and situational contexts. Cultural context pertains to the use of words related to the culture surrounding the production of the language. Meanwhile, within the situational context, the elements of field, tenor, and mode were identified. The Field in the short story "Senyum Karyamin" is evident in the choice of words related to the discourse discussed, such as pengepul (collector), pengumpul (gatherer), kubik (cubic), and so on. Additionally, the study found Tenor, specifically the use of language that illustrates social relationships between characters in the story. Finally, regarding Mode, the study identified both oral and written modes, with the oral mode being apparent in the use of direct quotation.